SEMIOTIC ANALYSIS AND VISUAL IDENTITY OF THE “PIA SARONDE” LOGO AS A BRANDING REPRESENTATION OF GORONTALO'S CULINARY UMKM (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This research explores the visual identity of the Pia Saronde brand—one of Gorontalo’s well-known local culinary products—by applying a semiotic perspective grounded in Roland Barthes’ theory. As a micro, small, and medium enterprise (MSME) operating in the food sector, the brand relies heavily on its logo to influence consumer impressions, reinforce its market positioning, and distinguish itself within a competitive business environment. The purpose of this study is to examine the structural components of the logo, analyze the denotative and connotative layers of meaning it conveys, and evaluate how effectively it reflects the cultural characteristics of the region. Using a qualitative descriptive approach, this study integrates visual examination of the logo with an extensive review of related literature. The analysis indicates that the logo’s yellow and brown color palette evokes a sense of warmth, sweetness, and culinary appeal, while its rounded typography suggests tradition, familiarity, and a homemade quality. Furthermore, the use of the name “Saronde” creates a symbolic linkage to the renowned Saronde Island, thereby strengthening the brand’s connection to its regional roots. Overall, the findings demonstrate that the logo successfully communicates both cultural and gastronomic associations. Nonetheless, the study recommends enhancing certain symbolic elements and improving adaptability for digital media to optimize the brand’s visual impact.